The Drivers of Climate Change Innovations: Evidence from the Australian Wine Industry - Galbreath, Jeremy; Charles, David; Oczkowski, E. (Springer Netherlands, 2014)
This study examined the drivers of climate change innovations and the effects of these innovations on firm outcomes in a sample of 203 firms in the South Australian wine cluster. The results of structural equation modeling analysis suggest that absorptive capacity has a direct effect on climate change innovations, and stimulates knowledge exchanges (KEs) between firms in the cluster. KEs between firms in the cluster in turn directly affect the climate change innovations. The findings suggest a perhaps counterintuitive interrelationship between firm- and cluster-level impacts, in which KEs between firms in the cluster play a partial mediating role in the innovation process. The study further finds that climate change innovations are related to firm performance (FP) and reductions in greenhouse gases (GHGs): mitigative innovations lead to greater GHG reductions while adaptive innovations impact on FP. Contributions of the findings are discussed, as are future research directions.